Dynamics of Agrarian Conflict the Kapa Village Community and PT PHP - Nila Sari; Yuhelna Yuhelna; Isnaini Isnaini; Erningsih Erningsih (Jurnal Mamangan, 2025)
ABSTRACT This research is motivated by the agrarian conflict between PT Permata Hijau Pasaman (PHP) and the community of Nagari Kapa, Luhak Nan Duo District, West Pasaman Regency. The conflict, which began in 1997, continues to drag on and has yet to find a complete resolution or a solution that can completely end the problem. The purpose of this research is to analyze the dynamics of this agrarian conflict by emphasizing how the customary land dispute has dragged on. The analytical framework uses Simon Fisher's conflict theory through the Stages of Conflict, which views conflict as a dynamic process ranging from pre-conflict, confrontation, crisis, outcome, to post-conflict. The research approach is qualitative with a descriptive type. Primary data was obtained through in-depth interviews with nine informants, while secondary data came from official documents, government archives, and related literature. Data analysis was carried out using the Miles and Huberman model through the stages of data collection, reduction, presentation, and conclusion drawing. The research results show that the conflict began with the handover of 1,600 hectares of customary land in 1997 without involving the entire community. The confrontation phase was evident through community rejection of the distribution of plasma land, which was deemed inconsistent with the agreement. The crisis peaked in 2024 when the company replanted land claimed by the community, leading to clashes with authorities. Efforts to resolve the conflict through village meetings, government mediation, and legal advocacy by civil society organizations have yielded no results. Keyword: Agrarian Conflict, Customary Land, Community